THE TRADITION OF THANKSGIVING IN THE MINAHASA COMMUNITY, NORTH SULAWESI: A REVIEW FROM THE HAPPINESS THEORY PERSPECTIVE: Tradisi Pengucapan dalam Masyarakat Minahasa, Sulawesi Utara: Tinjauan dari Teori Kebahagiaan - Stephanie Raqueen Inaray; Marselius Tondok (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The tradition of Thanksgiving in the Minahasa community, North Sulawesi, known as "Pengucapan," is a long-standing cultural practice that reflects gratitude for the blessings of harvests and other forms of livelihood. This research explores the tradition of Thanksgiving through the lens of the Gratitude Theory, as proposed by Emmons and McCullough (2003), which highlights the psychological and social benefits of expressing gratitude. The study uses a literature review methodology, drawing from articles, books, and other resources related to the Minahasa community and its Thanksgiving traditions. The results show that Pengucapan, initially rooted in agricultural practices, has evolved into a celebration that includes all forms of livelihood. It not only serves as an expression of gratitude to God but also strengthens social bonds within the community. The theory of gratitude explains that this collective expression of thankfulness enhances individual psychological well-being and fosters stronger social connections. This study provides new insights into how traditional practices like Pengucapan can positively impact mental health and social cohesion, offering a unique application of psychological theories to cultural rituals. Future research could further examine the role of gratitude in enhancing community life across different cultures